Evaluation of Electronic Scholarly Journals of Al-Neelain University in Sudan According to the Scopus Database Criteria - Dr. Omer Hassan Abdelrahman, Dr. Samir Ibrahim Bakhit & (COVENANT JOURNAL OF LIBRARY AND INFORMATION SCIENCE, 2019)
The main purpose of this study is to evaluate the online electronic scholarly journals of Al-Neelain University in Sudan according to the Scopus database criteria, with a view to investigating to what extent these journals meet the Scopus database criteria.Â  The study adopted the descriptive approach and case study method. The study population consisted of nine online scholarly journals all of which constituted the study sample. Data were collected by reviewing all online scholarly journals of the University. Data were then statistically analyzed using simple statistical tools and presented in tables. The findings indicated that all of Al-Neelain University online scholarly journals are compatible with Scopus criteria by 56.2%, and confirmed that the missing criteria included absence of publication ethics statement and lack of diversity in geographical distribution of editors in all journals. The study also revealed that 75% of the studied journals lack diversity in geographical distribution of authors and delays in the publication schedule, and that these journals are not available through quality websites. The study recommended the use of Scopus criteria for the development and improvement of Al-Neelain University online scholarly journals.